Signalling pathways and cellular functions of KDEL receptors: implications in cancer biology - Beatrice Dufrusine; Ilaria Cela; Chiara Gramegna Tota; Marta Palumbo; Michele Sallese (Cellular and Molecular Life Sciences)
Abstract KDEL receptors (KDELRs) are a small family of seven-transmembrane domain proteins primarily localized to the membranes of the Golgi apparatus and endoplasmic reticulum (ER). These receptors are responsible for retrieving ER-resident chaperones that have trafficked to post-ER compartments. Beyond their primary role in retrieval, chaperone binding to KDELRs trigger diverse signalling pathways. These include the activation of protein kinase A, Src tyrosine kinase, and Rab1a/Rab3a that are mediated respectively by the α-subunits Gαs, Gαq, and Gαo of heterotrimeric G-proteins. KDELR-activated signalling pathways regulate intracellular transport of proteins and membranes, extracellular matrix (ECM) degradation, and the formation of membrane protrusions from the plasma membranes. More recently, crosstalk with the EGF receptor has been reported, offering a potential explanation for how chaperones, often overrepresented on the plasma membrane of cancer cells, may contribute to enhanced cell proliferation. Reflecting their established cellular roles, numerous studies have documented significant involvement of these receptors in a broad spectrum of cancers including colorectal cancer, breast tumours, glioblastoma, melanoma, chondrosarcoma, and lung adenocarcinoma. The strong association between KDELRs and cancer is further highlighted by the observed correlation between KDELR expression and immune cell infiltration in tumours. This effect may arise from the influence of KDELRs on the secretory pathway, alongside the immunomodulatory role of KDELR1 within immune cells. In conclusion, endomembrane-initiated signalling through KDELR plays a pivotal role in regulating fundamental cellular processes, maintaining physiological functions, and modulating key aspects of cancer biology.